Exploring the Influence of Hookup Culture on Female and Male Rape Myths. Issue 9 (May 2021) - Reling, Timothy T.; Becker, Sarah; Drakeford, Leah; Valasik, Matthew
The present study systematically assesses the influence of hookup culture endorsement on the acceptance of female rape myths (i.e., false, stereotypical, or prejudicial beliefs regarding sexual assault involving female survivors) and male rape myths (i.e., false, stereotypical, or prejudicial beliefs about sexual assault involving male survivors). Multivariate regression analyses were conducted to assess the primary hypotheses that a particular form of hookup culture endorsement (i.e., the belief that hookups elevate an individual's social status) would act as the primary predictor of male and female rape myth acceptance among a sample of 376 U.S. college students. As with prior research, a complex relationship emerged for both male and female rape mythology in which acceptance increases or decreases based upon the form of hookup culture endorsement examined, as the endorsement of beliefs reflecting heterosexual power dynamics (e.g., harmlessness and status attainment) functioned as positive predictors of rape myth acceptance, while beliefs challenging such assumptions (e.g., sexual freedom) served to decrease rape myth acceptance. Results supported the primary hypotheses that beliefs concerning hookups and status attainment would be the largest predictor of male rape myth acceptance and female rape myth acceptance. Consistent with prior research, the predictive power of gender and religiosity was initially significant across both male and female rape myth acceptance yet diminished when controlling for levels of hookup culture endorsement. Furthermore, analyses indicated gender differences among the influences of hookup culture endorsement for female rape myth acceptance alone, as even though beliefs concerning status served as an aggravating factor for female rape myth acceptance, beliefs concerning sexual freedom served as a mitigating factor for women only.